Planning, shortage, and transformation : essays in honor of János Kornai - Kornai, János; Maskin, Eric; Simonovits, András (MIT Press, 2000)
The three major themes of János Kornai's work reflected in the title of this bookâ__planning, shortage, and transition, or transformationâ__figure prominently in the essays.